Efforts to improve ecotourism management for bekantan conservation from visitors' perspectives: a case study in Balikpapan East Kalimantan - Ardiyanto W Nugroho; Mukhlisi; Tri Atmoko (Foresty Faculty of Hasanuddin University, 2019)
The two fragmented mangrove forests, located in Graha Indah (HMGI) and Margomulyo (HMM) Balikpapan (East Kalimantan), are important habitats for Bekantan, an endemic and endangered animal species in Indonesian Borneo. The local government has put some conservation efforts by promoting those locations as the tourist destinations but they are not optimally well managed. This research aims to determine the visitors’ profiles, perceptions, and potential ticket funding by using questionnaires. Visitors’ ticket funding preferencewas obtained using the Willingness to Pay (WTP) method and analyzed using multiple regression analysis. Visitors’ profiles and perceptions were analyzed descriptively. The results showed that the visitors’ WTP in HMM and HMGI were Rp9.258 and Rp13.980, respectively, strongly influenced by income, type of jobs, and visiting frequency in HMGI. Meanwhile, HMM visitors were dominated by students (63%), with 11-20 years old by age (58%). On the other hand, the visitors’ occupation in HMGI was more varied i.e. private sectors (27%), students (27%) and civil servants (24%), with 21-30 years old by age (35%). Most of the visitors were from the city of Balikpapan that reached, 76% and 62% in HMM and HMGI, respectively. Potential funding from visitors cannot be estimated due to the lack of accurate data on the annual number of visitors. Internet and social media are potential methods to promote ecotourism in both places as well as promoting mangrove and bekantan conservation.